Door Opener or Waste of Time? The Effects of Student Internships on Labor Market Outcomes - Nils Saniter; Thomas Siedler (Institute for the Study of Labor (IZA), 2014)
This paper studies the causal effect of student internship experience on labor market choices and wages later in life. We use variation in the introduction and abolishment of mandatory internships at German universities as an instrument for completing an internship while attending university. Employing longitudinal data from graduate surveys, we find positive and significant wage returns of about six percent in both OLS and IV regressions. This result is mainly driven by a higher propensity of working full-time and a lower propensity of being unemployed in the first five years after entering the labor market. Moreover, former interns pursue doctoral studies less frequently. The positive returns are particularly pronounced for individuals and areas of study that are characterized by a weak labor market orientation. Heterogeneous effects are not found across other subgroups of the population.
Keywords: I23; J01; J31; 330; internships; skill development; higher education; labor market returns; instrument variable